Adipocyte CLDN5 promotes thermogenesis and energy expenditure through regulation of IL10 expression - Ke Feng; Wenqin Wang; Xianlong Gao; Hejie Yan; Mengyuan Xu; Baozhen Fan; Qianfeng Jia; Chao Wang; Jian Yu; Yi Li; Qinfeng Xu; Yanan An; et al. (Nature Communications)
Abstract The claudin protein family plays key roles in maintaining normal structure and function of epithelial and endothelial tight junctions. While several prior studies have addressed the expression of claudin in adipocytes that do not form tight junctions, here we demonstrate that CLDN5 is selectively expressed in non-thermogenic adipocytes within adipose tissue. Ablation of CLDN5 in adipocyte impairs thermogenesis and energy expenditure. CLDN5 deficiency also significantly increases diet-induced fat mass in mice, accompanied with glucose intolerance and insulin resistance. Mechanistically, CLDN5 affects the subcellular localization of Y-box protein 3, which directly regulates IL10 expression via binding to its promoter and specific sites in 3′-untranslated region, thereby acts in a paracrine manner to signal through IL10R in neighbouring thermogenic adipocytes. These findings expand our understanding about location and function of the extra-tight junction claudin proteins and provide molecular insights into signaling mechanisms underlying adipose thermogenesis that could inform future therapy.